2015
DOI: 10.3346/jkms.2015.30.8.1042
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Asthma Control by Stepwise Treatment in Elderly Asthmatic Patients

Abstract: The geriatric population is increasing, and asthma severity increases with age. We determined the predictors of asthma control, exacerbation, and the factors that affect asthma-specific quality of life (A-QOL) in elderly asthmatic patients. This was a prospective, multicenter, real-life study for 6 months with stepwise pharmacologic treatment based on the Global Initiative for Asthma (GINA) guideline. A total of 296 asthmatic patients aged ≥ 60 yr were recruited from 5 university centers in Korea. The improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Six publications found strong and consistent correlations between improvement in ACT score and improvement in ACQ score [8][9][10][11][12][13], with five of the publications assessing the statistical significance of the correlations. All five of these reports found statistically significant Number of asthma exacerbations 10 2 26,27 (2) 26,27 8 17,22,23,28-32 (7) 22,23,[28][29][30][31][32] Lung function 17 8 3,15,27,33-37 (5 b ) 3,34-37 9 11,13,18,38-43 (7 b ) 11,13,[38][39][40]42,43 General HRQoL 7 0 (0) 7 [49][50][51][52][53][54][55] (5 b ) 49,50,[52][53][54] Asthma-related QoL 7 5 28,34,[44][45][46] (5) 28,34,44-46 2 47,48 (2) 47,48 Sleep quality 6 2 45,56 (2) 45,56 5 [56][57]…”
Section: Act Score and Asthma Symptom Controlmentioning
confidence: 96%
See 1 more Smart Citation
“…Six publications found strong and consistent correlations between improvement in ACT score and improvement in ACQ score [8][9][10][11][12][13], with five of the publications assessing the statistical significance of the correlations. All five of these reports found statistically significant Number of asthma exacerbations 10 2 26,27 (2) 26,27 8 17,22,23,28-32 (7) 22,23,[28][29][30][31][32] Lung function 17 8 3,15,27,33-37 (5 b ) 3,34-37 9 11,13,18,38-43 (7 b ) 11,13,[38][39][40]42,43 General HRQoL 7 0 (0) 7 [49][50][51][52][53][54][55] (5 b ) 49,50,[52][53][54] Asthma-related QoL 7 5 28,34,[44][45][46] (5) 28,34,44-46 2 47,48 (2) 47,48 Sleep quality 6 2 45,56 (2) 45,56 5 [56][57]…”
Section: Act Score and Asthma Symptom Controlmentioning
confidence: 96%
“…Ten studies reported on the relationship between improvement in ACT score and reduction in asthma exacerbations (Table 1) [17,22,23,[26][27][28][29][30][31][32].…”
Section: Act Score and Asthma Exacerbationsmentioning
confidence: 99%
“…Many questions remain unanswered in elderly patients, as this population is partially excluded from randomized clinical trials due to age criteria and comorbidities. A recent study examined the predicators of asthma control in elderly patients with asthma in South Korea 5253. This study showed that the number of medications for comorbidities, as well as functional status, determined by the higher physical functioning scale, are important parameters in assessing and predicting asthma control 53.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…A recent study examined the predicators of asthma control in elderly patients with asthma in South Korea 5253. This study showed that the number of medications for comorbidities, as well as functional status, determined by the higher physical functioning scale, are important parameters in assessing and predicting asthma control 53. A large number of medications were associated with unfavorable outcomes, and it is recommended that treatment regimens for the elderly should be as simple as possible for elderly asthmatic patients.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Poor asthma control is associated with increased risk of exacerbations, debilitation, impaired quality of life, increased healthcare utilization and reduced productivity [10,11,17]. The degree of asthma control appears to have a significant impact on health-related quality of life [7].…”
Section: Introductionmentioning
confidence: 99%